Fotocatalisadores a base de dióxido de titânio modificados com nióbio para redução de gás carbônico a metanol - Nogueira, Marcelo Vianna [UNESP] (2014)
This work was based on synthesis of TiO2 photocatalysts powders modified with Nb structurally by Pechini and superficially by metallic Nb depositing by sputtering, characterization of these photocatalysts powders to verify these changes, and evaluation of photocatalytic activity in the reduction of CO2 to methanol and decolorization of of dye rhodamine-B solutions. The TiO2 modification tries to achieve an increase in the recombination time of the electron-hole pair and hence a higher photocatalytic activity. The modification to replace Ti4+ by Nb5+ aims to promote the generation of donor levels of electrons in the crystal structure and modification for nanoparticles deposition of metallic Nb by sputtering to act as acceptor of electrons on the photocatalysts powders surface, changes them, who will serve in reducing CO2. Starting from these premises first photocatalysts powders were synthesized in the compositions of 0.0 %, 0.5 %, 1.0 %, 2.5 % (w/w) of Nb and subsequently 5.0% , 10.0 % and 20.0% (w/w) of Nb with the methods mentioned. The photocatalysts powders were characterized using X-ray diffraction (XRD-Rigaku Rint-2000) , surface area SBET (EST-Micrometrics ASAP 2010) , Raman spectroscopy (HORIBA HR-800 ) , FEG / SEM (JEOL JSM-7500F) and XPS (UNI-SPECS UHV) to analyze the surface characteristics. After characterizing the photocatalysts poder underwent two photocatalytic tests. The first to assess the occurrence of CO2 reduction and the second aimed at evaluating the capacity in the oxidative bleaching of the dye rhodamine-B using spectroscopy in the UV-vis region to obtain the results. To verify and quantify the possible formation of carbonyl and alcohol radicals, each sample was analyzed for TOC (Aurora Analytical model HI 1030) and FID-GC (Varian CP- 3800). Through the techniques used for characterization of photocatalyst powders was observed that the predominant crystalline phase is anatase and Ti was replaced by Nb...